Using livestreaming technology to connect the public with secretive and maligned animals - Bachhuber, Owen M.; Roberts, Max C.; Singer, Ryan M.; Brewster, Doug R.; Brewster, Rob A.; Dunham, Kevin K.; Boback, Scott M.; Taylor, Emily N. (Frontiers in Amphibian and Reptile Science, 2025)
As people become increasingly disconnected from nature, novel approaches are needed to facilitate empathy and conservation action for wildlife. Recent advances in livestreaming cameras enable the public’s observation of wild animals in real time and facilitate engagement in community science. In 2024, we launched an off-grid livestreaming camera at a rattlesnake mega-den in Colorado, where hundreds of snakes emerge in the spring and dozens of females rest for the summer and prepare to give birth in the fall. This paper provides the first detailed description of the equipment and setup needed for remote, off-grid camera livestreaming. The camera continually streamed live to YouTube over the snakes’ active season (May 15 through November 5). During this time, a group of students and volunteers operated the camera and moderated a live-chat by interacting with viewers and answering questions. YouTube comments reflected a feeling of community among the viewers, and many of them contributed to data collection from the livestream as community scientists. Media coverage of the livestream resulted in increased viewership. Livestreaming technology shows great potential for showcasing animal aggregations, connecting the public with nature and scientific research, and improving the public perceptions of unpopular animals like rattlesnakes.